Investigating the Relationship between Types of Deprivation and Social Tolerance among Citizens of Tehran - Negar Firouzeh; Khadijeh Safiri (Strategic Research on Social Problems)
IntroductionIn today's vibrant, diverse, and heterogeneous societies, establishing a democratic culture and promoting sustainable development require the predominance of social tolerance. This involves accepting differences, recognizing the rights of those who are dissimilar, and fostering peaceful coexistence. The rising tide of domestic political strife and social upheaval marked by racism, genocide, and war in many countries underscores the urgent need to promote ideas of peace and tolerance. Cultivating such a culture is vital for the well-being of individuals, families, organizations, states, and society as a whole. The salvation of humanity hinges on the establishment of a culture rooted in peace and tolerance; conversely, a culture of war and intolerance threatens to lead humanity to collective destruction (Agius & Ambrosewicz, 2003, pp. 4-5). Furthermore, the onset of modernity, proliferation of international communication, urbanization, and the consequent rise in immigration and ethnic diversity have resulted in confrontations among differing and often conflicting individuals. If these individuals fail to navigate their differences and strive for uniformity in a pluralistic society, the likelihood of conflict and violence will escalate (Nikkhah et al., 2020, p. 147). Given the significance of this issue, the primary objective of the current research was to investigate how deprivation of resources and opportunities across multiple domains affected individuals' levels of tolerance and their actions. Ultimately, this could influence the propensity for misbehavior or violence.  Materials & MethodsTo achieve this, we analyzed and synthesized various theories on deprivation and tolerance, focusing particularly on comprehensive and multidimensional frameworks proposed by theorists, such as Parsons, Bourdieu, Maslow, Inglehart, and Chalabi. We collected data using a survey technique, employing multiple-stage cluster sampling across 5 selected regions, involving 400 citizens of Tehran aged 18 to 64 years. The validity and reliability of the survey instrument were rigorously assessed, emphasizing content validity, construct validity, and Cronbach's alpha coefficient. Additionally, during the pre-test phase, we conducted exploratory interviews with 14 residents of Tehran to confirm and further investigate specific dimensions and components of tolerance and deprivation. The Cronbach's alpha values for the key constructs of the study—including total social tolerance, identity tolerance, moral-behavioral tolerance, political tolerance, environmental tolerance, and various forms of deprivation (economic, cultural, social, political, physical-mental, ethical, environmental-physical, and feelings of relative deprivation)—demonstrated strong reliability, with values exceeding 70 percent. Discussion of Results & ConclusionThe findings of this research indicated that the level of social tolerance among citizens of Tehran was below average. This could be attributed to the prevalence of regressive discourse and an ideology focused on preserving traditions, which stood in opposition to the discourse of change—particularly among the younger generation in immigrant-receiving metropolises like Tehran. This dynamic ultimately contributed to the emergence of a dual anomic society, where Iranian society remained caught between traditional, modern, and postmodern values. Furthermore, the institutionalization of unchanging values and norms from the dominant discourse, as well as traditional moral patterns—especially concerning clothing, behavior, and sexual relations—hindered a segment of society from embracing the transition to a modernized or postmodernized world. This resistance to new behavioral patterns could lead to increased conflicts, tensions, and intolerant behaviors.In terms of deprivation, while economic deprivation was rated as approximately average, other forms—particularly political, ethical, and social deprivation—were reported to be above average among the citizens.A significant correlation existed between cultural, social, economic, political, and ethical deprivation, as well as feelings of relative deprivation (in comparison to others), and social tolerance. Specifically, as these forms of deprivation increased (excluding political deprivation), social tolerance tended to decrease. Conversely, an increase in political deprivation correlated with an increase in social tolerance. This positive and significant relationship between political deprivation and social tolerance could be understood in the context of societal bipolarity and the widening gap between the state and its citizens. The failure to fulfill ideals, democratic values, and citizen rights had led to a crisis of legitimacy for the state. Consequently, dissatisfaction with the state's inability to address problems and crises had resulted in citizens withholding their support. In this context, two potential responses from citizens could be anticipated. First, they might perceive the government and its representatives as outsiders or, more accurately, as an out-group. This perception could strengthen their in-group connections (among people), leading them to consciously practice active tolerance—either abstractly (verbally endorsing tolerance) or objectively (verbally and practically demonstrating tolerance)—especially regarding the rights of more vulnerable groups that received less respect from the government. Alternatively, citizens might experience a form of learned helplessness due to political deprivation, resulting in either active (particularly abstract) or passive tolerance.Moreover, the strongest independent variables identified in the regression analysis of social tolerance included cultural, ethical, political, and social deprivation. The adjusted R-squared value indicated that 28.2% of the variance in social tolerance was accounted for by these independent variables. Structural Equation Modeling (SEM) further supported the construct validity of the measurement tool (measurement model) and highlighted the significant impact of cultural, ethical, political, and social deprivation on social tolerance (structural model), aligning with the findings from the multiple regression analysis.